Avaliação de um dessalinizador solar com recuperação de calor com novo arranjo do circuito de aquecimento para operação com óleo térmico - Pinho, Diego Caitano de (2017)
Due to the increasing demand for potable water, as well as the rising levels of pollution in natural water reservoirs, performance improvements in a solar thermal desalination system with heat recovery tower is not only a challenge, but also a necessity. The solar desalination system studied has two main units: a heating unit and a desalination unit. The heating unit has three flat solar collectors, two of these made in Europe as part of another project, and the third one was manufactured in the solar laboratory. The desalination unit consists of a one storage tank and seven desalination stages, each with its own tray. Among other modifications, the main difference between the present system and its predecessors was the use of a heat exchanger inside the storage tank. Thus, the solar radiation absorbed by the collectors was transferred in the heat exchanger (made of a copper pipes) to the water stored in the tank, mainly by conduction and forced convection. An oil pump was responsible for the flow of the thermal oil through the closed circuit of the heating unit. Part of the heated water stored in the tank evaporated, rose, and condensed on the lower surface of the less heated tray of the first stage above, heating the brackish water in this tray. The present dissertation evaluated the solar desalination system with heat recovery, operating with the modifications presented and a synthetic thermal oil flow (Dowtherm A) as the working fluid. To characterize the performance of the thermal desalination system, the water production and its quality were measured for two different water supply conditions to the tower: continuous feed and intermittent feed. The system was also tested with flat plate reflectors fixed on the solar collector. Two important parameters, the Output Gain Ratio (GOR) and the Performance Coefficient (COP) were determined. The best desalinate water (almost pure) production was 34 L per day (198.1 mL / MJ) with an average electrical conductivity of 14.9 μS / cm (equivalent to 9.5513 ppm). On this day, the GOR and COP were 0.44 and 4.41, respectively. The system is in conditions to be tested in communities where there is a good level of solar radiation and saltwater resources.